Feeding Value of Raw or Enzyme Treated Dandelion Leaves and Fenugreek Seeds Alone or in Combination in Meat Type Chicken - Qureshi, Saim; Banday, M.T.; Shakeel, Irfan; Adil, S. (Pakistan Journal of Nutrition, 2015)
A study was conducted to evaluate the feeding value of dietary supplementation of locally available herbs Dandelion leaves and Fenugreek seeds with or without enzyme treatment in meat type chicken. To achieve the envisaged objective, two hundred seventy three day old commercial broiler chicks were procured from a reputed source and reared together until 7 days of age. On 7th day, the chicks were individually weighed, distributed randomly into 7 groups of 3 replicates with 13 chicks each. Birds in the control group were fed diets without additives (T1). The other 6 treatment groups were fed the basal diet supplemented with 0.5% Dandelion leaves (T2), 1% Fenugreek seeds (T3), combination of 0.5% Dandelion leaves and 1% Fenugreek seeds (T4), Enzyme treated Dandelion leaves 0.5% (T5), Enzyme treated Fenugreek seeds 1% (T6) and combination of Enzyme treated Dandelion leaves (0.5%) and (1%) Fenugreek seeds (T7). There was no significant (p>0.05) effect on the carcass characteristics of chicken among various treatment groups and control except for the dressing percentage and length of various segments of small intestine which were significantly (p<0.05) higher in the groups raw or enzyme treated Dandelion leaves and Fenugreek seeds. Highest values were achieved in group fed combination of enzyme treated Dandelion leaves and Fenugreek seeds (T7). Reduction in the feed cost per kg live weight gain among different treatment groups was observed when compared with the control group. Among different treatment groups, compared to control an additional profit of Rupees (Rs) 884 per 100 kg body weight was achieved in the group fed enzyme treated 0.5% Dandelion leaves (T5), followed by Rs. 849 in the group fed enzyme treated 1% Fenugreek seeds (T6). In conclusion, 0.5% Dandelion leaves and 1% Fenugreek seeds treated with enzymes may be incorporated in the diet in order to economize the meat type chicken production.